Ultrawide‐Bandgap Semiconductors: Research Opportunities and Challenges. (4th December 2017) - Tsao, J. Y.; Chowdhury, S.; Hollis, M. A.; Jena, D.; Johnson, N. M.; Jones, K. A.; Kaplar, R. J.; Rajan, S.; Van de Walle, C. G.; Bellotti, E.; Chua, C. L.; Collazo, R.; et al.
Abstract: Ultrawide‐bandgap (UWBG) semiconductors, with bandgaps significantly wider than the 3.4 eV of GaN, represent an exciting and challenging new area of research in semiconductor materials, physics, devices, and applications. Because many figures‐of‐merit for device performance scale nonlinearly with bandgap, these semiconductors have long been known to have compelling potential advantages over their narrower‐bandgap cousins in high‐power and RF electronics, as well as in deep‐UV optoelectronics, quantum information, and extreme‐environment applications. Only recently, however, have the UWBG semiconductor materials, such as high Al‐content AlGaN, diamond and Ga2 O3, advanced in maturity to the point where realizing some of their tantalizing advantages is a relatively near‐term possibility. In this article, the materials, physics, device and application research opportunities and challenges for advancing their state of the art are surveyed. Abstract : Ultrawide‐bandgap (UWBG) semiconductors, with bandgaps significantly wider than the 3.4 eV of GaN, represent an exciting and challenging new area of research in semiconductor materials, physics, devices and applications. This article surveys and presents an enumerated list of the materials, physics, device and associated application research opportunities and challenges important for advancing the state of their science and technology.